Ab initio approach to the effect of Fe on the diffusion in hcp Zr II: The energy barriers - Pasianot, Roberto Cesar (2009)
Using density functional theory calculations together with the Monomer method for the search of saddlepoints (combined for the first time with an ab initio algorithm), we obtain the vacancy formation energiesand the migration barriers for a-Zr self-diffusion and for the diffusion of interstitial impurities, includingthe ultra-fast diffuser Fe. Good agreement with measured diffusion coefficients is obtained, as a muchlower energy barrier for the ultra-fast diffuser is found. We also suggest a possible mechanism for theincrease in self-diffusion due to the Fe impurity, always present in the experimental samples.